Participatory On-farm Evaluation and Demonstration of Groundnut Varieties in Abaya Woreda of Borana Zone - Abdulla, Ahmed Mohammed; Aliyi, Ibsa; Desiso, Feyissa (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
The research activity was carried out with the objective of evaluating and identifying adaptable and improved groundnut varieties and to familiarize farmers with groundnut production techniques. It was executed at Abaya woreda of Borana Zone for two years (2012/13-2014/15). A multidisciplinary team composed of breeder, pathologist, agronomist and agricultural extensionist was closely working both with the farmers and woreda agricultural experts and DAs. Regular visits, trainings and field days were conducted to provide for interaction among researchers, extension workers and farmers. The variety selection process was carried out from different dimensions including utilization, marketing and field performance. In general, color, size, market demand were identified as important farmer criteria. The other important criteria were related to field performance of the variety that includes: yield and tolerance to disease and insect pest followed by maturity period. Using these criteria the farmers identified varieties that suit their respective location. Accordingly, Abaya farmers showed special interest to Tole-1, Fayo and NC4x. The most interesting part of the finding was that most of the varieties preferred from utilization and marketing angle were also found superior in their field performance. Side by side, with the aim of strengthening local availability of seeds of preferred varieties, farmer based seed production was launched and the seed produced thereby was distributed both in cash and kind from farmers to farmers. Moreover, by way of revolving seed it was attempted to redistribute the seed to other non participant farmers in the area. In so doing both awareness and access to the technology was improved.